Brillouin microscopy for the evaluation of hair micromechanics and effect of bleaching. Issue 6 (5th April 2021) - Correa, Noemi; Alunni Cardinali, Martina; Bailey, Michelle; Fioretto, Daniele; Pudney, Paul D. A.; Palombo, Francesca
Abstract: Brillouin microscopy is a new form of optical elastography and an emerging technique in mechanobiology and biomedical physics. It was applied here to map the viscoelastic properties of human hair and to determine the effect of bleaching on hair properties. For hair samples, longitudinal measurements (i.e. along the fibre axis) revealed peaks at 18.7 and 20.7 GHz at the location of the cuticle and cortex, respectively. For hair treated with a bleaching agent, the frequency shifts for the cuticle and cortex were 19.7 and 21.0 GHz, respectively, suggesting that bleaching increases the cuticle modulus and—to a minor extent—the cortex modulus. These results demonstrate the capability of Brillouin spectroscopy to address questions on micromechanical properties of hair and to validate the effect of applied treatments. Abstract : This article reports a proof‐of‐concept study of hair micromechanics and effect of bleaching using spontaneous Brillouin microscopy at high contrast and high spectral resolution. Results demonstrate that Brillouin is capable of resolving the hair main structures, i.e. cuticle and cortex, through marked differences in acoustic properties measured at gigahertz frequencies: the Brillouin shift, related to the longitudinal elastic modulus, and the Brillouin linewidth, which yields the apparent viscosity.